The growth of tree legume fodder Indigofera zollingeriana at various levels of drought stress treatment - Iwan Herdiawan (Indonesian Center for Animal Research and Development (ICARD), 2013)
The research aimed to determine growth of the forage tree legume Indigofera zollingeriana on different drought stress treatments. The study was done based on completely randomized design (CRD), with 12 plants as replications. The treatment consisted of three levels of drought stress, ie control (100% field capacity=fc), moderate drought stress (50% fc), and severe drought stress (25% fc). The variables observed were plant height, stem diameter, number of branches, biomass production, shoot dry weight, root dry weight, shoot/root ratio, and root length. The data were analyzed by covariance analyzed (ANOVA) and the differences between the treatments were tested by LSD. The results showed that moderat drought stress (50% fc) and severe drought stress (25% fc) significantly (P < 0.01) decreased length and height of plant, stem diameter, number of branches, biomass production, shoot dry weight, root dry weight, but not shoot or root ratio. Key words: Indigofera zollingeriana, Drought Stress, Growth